2021
DOI: 10.1038/s41598-021-96892-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum soluble (pro)renin receptor level as a prognostic factor in patients undergoing maintenance hemodialysis

Abstract: The (pro)renin receptor [(P)RR)] is a multifunctional protein that is cleaved to generate the soluble (P)RR [s(P)RR], reflecting the status of the tissue renin-angiotensin system and/or activity of the (P)RR. The serum s(P)RR level is associated with arteriosclerosis, independent of other risk factors, in patients undergoing hemodialysis (HD). This study was conducted to investigate whether the s(P)RR level was associated with new-onset cardiovascular events or malignant diseases and poor prognosis in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Previous observations have linked (P)RR polymorphisms to BP levels in Japanese men (mean age 61.1 ± 9.6 years) [ 43 ] and white men (mean age, 45.4 ± 14 years) [ 44 ], while in animals s(P)RR was positively associated with systolic BP [ 16 ]. Recently, Amari et al [ 45 ] showed that s(P)RR is associated with cardiovascular events and mortality, serving as a biomarker to identify patients that require intensive care. The study population was older, with a number of CVDs and undergoing hemodialysis [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous observations have linked (P)RR polymorphisms to BP levels in Japanese men (mean age 61.1 ± 9.6 years) [ 43 ] and white men (mean age, 45.4 ± 14 years) [ 44 ], while in animals s(P)RR was positively associated with systolic BP [ 16 ]. Recently, Amari et al [ 45 ] showed that s(P)RR is associated with cardiovascular events and mortality, serving as a biomarker to identify patients that require intensive care. The study population was older, with a number of CVDs and undergoing hemodialysis [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Amari et al [ 45 ] showed that s(P)RR is associated with cardiovascular events and mortality, serving as a biomarker to identify patients that require intensive care. The study population was older, with a number of CVDs and undergoing hemodialysis [ 45 ]. Our study already points to the usefulness of s(P)RR as a biomarker even in a healthy, young population (aged 20–30 years) with no current or historic CVD.…”
Section: Discussionmentioning
confidence: 99%